2014
DOI: 10.1111/ejss.12160
|View full text |Cite
|
Sign up to set email alerts
|

Mapping contaminated soils: using remotely‐sensed hyperspectral data to predict pH

Abstract: Summary This study assessed the feasibility of remote mapping and, thus, monitoring of soils contaminated by acid mine drainage. We report on the use of laboratory and airborne spectroscopy to determine pH. Reflectance spectra were obtained for rock and soil samples collected at our test site, the abandoned Brukunga Pyrite Mine in South Australia, using a laboratory‐based Analytical Spectral Devices Inc. (ASD) spectroradiometer. A partial least squares (PLS) regression was used to develop a predictive equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…As a result, the PLSR models based on the HSI-resampled spectra from 505 nm to 956 nm to estimate soil pH exhibited good performance in this study. Similar results are reported in other studies [ 34 , 51 , 52 ]. This case can be attributed to (1) the good correlation between the soil alkalinity and soil color; and (2) a decrease in the soil reflectance with increasing soil alkalinity in the VIS-NIR wavelengths.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, the PLSR models based on the HSI-resampled spectra from 505 nm to 956 nm to estimate soil pH exhibited good performance in this study. Similar results are reported in other studies [ 34 , 51 , 52 ]. This case can be attributed to (1) the good correlation between the soil alkalinity and soil color; and (2) a decrease in the soil reflectance with increasing soil alkalinity in the VIS-NIR wavelengths.…”
Section: Discussionsupporting
confidence: 93%
“…Using HSI images to estimate soil alkalinity and salinity can be attributed to the sensitivity of spectral reflectance to these soil properties, especially in certain wavelengths. Past studies [ 53 ] have used the PLSR regression coefficients to approximate the strength of sensitivity for each soil factor, such as soil pH [ 35 , 51 , 54 ] and salts [ 27 ]. In this study, three HSI bands in green, red, and NIR regions had the most important contribution to soil pH and EC estimation.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coefficients in VIS and NIR bands were higher than those in SWIR bands. Our findings were in agreement with Ong and Cudahy [31], Lopez-Granados et al [50], and Stoner [51] who found that spectral variations in 350-1200 nm were highly related to the changes of the soil pH, and the relationships were much higher in shorter wavelengths. According to Bear [52], organic matter, water, and oxidation were influencing factors of pH and color association.…”
Section: Potential Use Of Soil Spectra For Soil Alkalinity and Salinisupporting
confidence: 93%
“…As shown in Table 2 commonly accepted as the boundary between saline and non-saline soils [31]. Most soils in the study area were characterized as non-saline soils.…”
Section: Salinity and Alkalinity Properties Of Soil Samplesmentioning
confidence: 95%
“…Articles by Rivera Villarreyes et al (), Eliran et al () and Ong & Cudahy () tested the application of proximal sensing by using emerging techniques such as cosmic rays, sub‐millimetre wavelengths and optical spectroscopy. Cosmic rays were used to estimate root‐zone soil hydraulic properties.…”
Section: Overview Of Papersmentioning
confidence: 99%